Mandating the Use of Proximity Tracking Apps During Coronavirus Disease 2019: Ethical Justifications - Dave, Riya; Gupta, Rashmi (Frontiers in Medicine, 2020)
The rise of the COVID-19 in a digital world has expectedly called upon technologies, such as wearables and mobile devices, to work in conjunction with public health interventions to tackle the pandemic. One significant example of this integration is the deployment of proximity tracing apps on smartphones to enhance traditional contact tracing methods. Many countries have adopted proximity tracking apps, however, there is a large degree of global differentiation in the voluntariness of the apps. Further, the concept of a mandatory policy—forcing individuals to use the apps—has been met with ethical concerns (e.g. privacy and liberty). While ethical considerations surrounding deployment have been put forth, such as by the World Health Organization, ethical justifications for a mandatory policy are lacking. Here we use the Faden-Shebaya framework, which was formed to justify public health interventions, to determine if the compulsory use of proximity tracking apps is ethically appropriate. We show that while theoretically justified, due to the current state of proximity tracking applications and societal factors, it is difficult to defend a mandatory policy in practice.